Occurrence of Escherichia coli O157:H7 in cattle feces and contamination of carcass and various contact surfaces in abattoir and butcher shops of Hawassa, Ethiopia. Issue 1 (December 2017) - Atnafie, Biruhtesfa; Paulos, Degmawi; Abera, Mesele; Tefera, Genene; Hailu, Dereje; Kasaye, Surafel; Amenu, Kebede
Abstract Background Despite of the sanitation measures in municipal abattoirs to reduce contamination, Escherichia coli continues to be a health hazard. The present study was conducted on 150 apparently healthy slaughtered cattle at municipal abattoir and in 50 different butcher shops in Hawassa town, Ethiopia. The objectives of the study were investigating the occurrence and antimicrobial resistance ofE. coli O157:H7 isolated from fecal samples, carcasses swab, contacts surfaces (swabs of meat handlers hands, knife and clothes of meat transporters) as well as from butcher shops (meat samples, swabs from cutting board swab, butcher men hand and knife surface).E. coli O157:H7 was isolated and identified using bacteriological culture, biochemical tests and Biolog identification system. AllE. coli O157:H7 isolates were then checked for their antimicrobial susceptibility pattern using eleven selected antimicrobial discs. Results Of the entire set of 630 samples, 2.4% (15/630) (95% CI = 1.3–3.9%) were positive forE. coli O157:H7. When disaggregated by the sources of the samples, E. coli O157:H7 were prevalent in 2.8% (11 of 390) of the abattoir samples, of which 4.7% of the fecal sample and 2.7% of the carcass swabs. AndE. coli O157:H7 were positive in 1.7% (4 of 240) of butcher shop specimens of which 2% of meat sample and 3.3% of Cutting board swabs. No statistically significant difference in the prevalence ofE. coli 0157: H7 between sex, origin, and breed of cattle. The isolatedE. coli O157:H7 were found to be100% susceptible to cefotaxime, ceftriaxone, gentamycin, kanamycin and nalidixic acid. Conclusion This study concludes the occurrence ofE. coli O157:H7 and the presence of multiple antibiotic resistance profiles in cattle slaughtered at Hawassa municipal abattoir and retail meat sold at butcher shops. This indicates high risk to public health especially in Ethiopia where many people consume raw or under cooked meat. Regulatory control of antibiotics usage in livestock production and pharmaco-epidemiological surveillance in food animals and animal products is hereby recommended to ensure consumer safety.